Say it ain't so, Joe! : the true story of Shoeless Joe Jackson - Gropman, Donald (Secaucus, NJ Citadel Press, 1979)
This immensely readable biography tells the story of Shoeless Joe Jackson, generally considered baseball's greatest natural hitter ever--but who was implicated in the most notorious sports scandal in American history.
D., 5/03
Keywords: Jackson, Joe, 1888-1951; Baseball players--United States--Biography